(untitled) (Ameghiniana, 2017)
Nothrotherium maquinense, Ahytherium aureum and Australonyx aquae are ground sloths endemic of the late Pleistocene of the Brazilian Intertropical Region for which, as opposed to other xenarthrans such as megatheriid sloths and glyptodonts, no information regarding pathological conditions is available. Herein, we describe, based on an anatomopathological examination, four types of lesions for N. maquinense (spondyloarthropathy, Schmorl’s node, vertebral trauma and unspecific infection) and one lesion for A. aureum (osteochondritis dissecans). No lesions were observed in A. aquae. Although several different diseases have been diagnosed, considering the significant number of specimens (2,232) and individuals (41) analyzed, low prevalence marks them all. ELUCIDANDO LAS ENFERMEDADES ÓSEAS DE LOS PEREZOSOS PLEISTOCÉNICOS BRASILEÑOS: LOS PRIMEROS CASOS REGISTRADOS EN LA FAMILIAS NOTHROTHERIIDAE Y MEGALONYCHIIDAE. Nothrotherium maquinense, Ahytherium aureum y Australonyx aquae son perezosos endémicos del Pleistoceno tardío de La Región Intertropical Brasileña para los cuales no hay información acerca de las condiciones patológicas, en contraste con otros xenartros, tales como los perezosos megatériideos y gliptodontes. Aquí se describen cuatro tipos de lesiones en N. maquinense (espondiloartropatía, nódulo de Schmorl, traumatismo de la médula e infección no específica) y una lesión en A. aureum (osteocondritis disecante) sobre la base de un examen patológico. Ninguna lesión se halló en A. aquae. Aunque muchas enfermedades diferentes han sido diagnosticadas, muestran un baja predominio, teniendo en cuenta el gran número de especímenes (2.232) e individuos (41) analizados.